Assessing completeness of patient medical records of surgical and obstetric patients in Northern Tanzania. Issue 1 (31st December 2020) - Lodge, William; Menon, Gopal; Kuchukhidze, Salome; Jumbam, Desmond T.; Maongezi, Sarah; Alidina, Shehnaz; Nguhuni, Boniface; Kapologwe, Ntuli A.; Varallo, John
ABSTRACT: Background: Strengthening surgical services in resource-constrained settings is contingent on using high-quality data to inform decision making at clinical, facility, and policy levels. However, the evidence is sparse on gaps in paper-based medical record quality for surgical and obstetric patients in low-resource settings. Objective: We aim to examine surgical and obstetric patient medical record data quality in health facilities as part of a surgical system strengthening initiative in northern Tanzania. Methods: To measure the incidence of Surgical Site Infections (SSIs), sepsis and maternal sepsis surgical and obstetric inpatients were followed prospectively, over three months in ten primary, district, and regional health facilities in northern Tanzania. Between April 22nd to May 1st, 2018, we retrospectively reviewed paper-based medical records of surgical and obstetric patients diagnosed with SSIs, post-operative sepsis, and maternal sepsis in the three-month follow-up period. A data quality assessment tool with18 data elements related to documentation of SSIs and sepsis diagnosis, their respective symptoms and vital signs, inpatient daily monitoring indicators, and demographic information was developed and used to assess the completeness of patient medical records. Results: Among the 157 patients diagnosed with SSI and sepsis, we found and reviewed 68% of all medical records. Among records reviewed, approximately one third (34%) and one quarter (23%) included documentation of SSI and sepsis diagnoses, respectively. 6% of reviewed records included documentation of all SSI and sepsis diagnoses, symptoms and vital signs, inpatient daily monitoring indicators, and demographic data. Conclusions: Strengthening data quality and record-keeping is essential for surgical team communication, continuity of care, and patient safety, especially in low resource settings where paper-based records are the primary means of data collection. High-quality primary health information provides facilities with actionable data for improving surgical and obstetric care quality at the facility level.